Tuning the Redox Chemistry of a Cr/SiO2 Phillips Catalyst for Controlling Activity, Induction Period and Polymer Properties. Issue 15 (6th July 2020) - Jongkind, Maarten K.; van Kessel, Theo; Velthoen, Marjolein E. Z.; Friederichs, Nic.; Weckhuysen, Bert M.
Abstract: The Cr/SiO2 Phillips catalyst has taken a central role in ethylene polymerization ever since its discovery in 1953. This catalyst is unique compared to other ethylene polymerization catalysts, since it is active without the addition of a metal‐alkyl co‐catalyst. However, metal‐alkyls can be added for scavenging poisons, enhancing the catalyst activity, reducing the induction period and altering polymer characteristics. Despite extensive research into the working state of the catalyst, still no consensus has been reached. Here, we show that by varying the type of metal‐alkyl co‐catalyst and its amount, the Cr redox chemistry can be tailored, resulting in distinct catalyst activities, induction periods, and polymer characteristics. We have used in‐situ UV‐Vis‐NIR diffuse reflectance spectroscopy (DRS) for studying the Cr oxidation state during the reduction by tri‐ethyl borane (TEB) or tri‐ethyl aluminum (TEAl) and during subsequent ethylene polymerization. The results show that TEB primarily acts as a reductant and reduces Cr 6+ with subsequent ethylene polymerization resulting in rapid polyethylene formation. TEAl generated two types of Cr 2+ sites, inaccessible Cr 3+ sites and active Cr 4+ sites. Subsequent addition of ethylene also revealed an increased reducibility of residual Cr 6+ sites and resulted in rapid polyethylene formation. Our results demonstrate the possibility of controlling the reduction chemistry by adding the proper amount and type of metal‐alkyl for obtaining desired catalyst activities and tailored polyethylene characteristics. Abstract : Role of Metal‐alkyls in Phillips catalysts : Combining batch‐ethylene polymerization reactions with in‐situ UV‐Vis‐NIR diffuse reflectance spectroscopy experiments of an industrial Cr/SiO2 Phillips catalyst allowed for correlating the decreased induction period and increased catalyst activity to metal‐alkyl induced changes in the Cr reduction chemistry.